Centering Primary Health Care (PHC) Nurses' experiences in their practice of policy implementation - TB diagnostic policy reform in the Western Cape, South Africa - Louskieter, Lance (Department of Public Health and Family Medicine, 2019)
This project focused on the recent global reforms in TB diagnostic policy and the implementation of Xpert MTB/RIF (GeneXpert) diagnostic technology into the health system, as a case to assess the extent to which software issues - particularly the human qualities of the system – mediates policy implementation. It centres the experiences of frontline workers in local implementation contexts as imperative because of frontline workers’ have discretionary power and influence in their practice. The premise of this mini-dissertation is that researchers and policy makers should centre the lived experiences of service delivery level health workers when implementing policy or programmatic reforms. This may deepen people-centred approaches which is essential for health systems strengthening. This mini-dissertation is structured into three parts: Part A: This is the research protocol that was submitted for ethical review and approval to the Faculty of Health Science Ethical Review Committee (FHSERC). The protocol frames the study objectives and the initial intentions of the research study. The justifications for the research question, theoretical framework, the research design, methods for data collection and analysis and timelines are clearly presented and discussed. Part B: Using GeneXpert policy reform implementation as a pathfinder, this section presents an undertaking of a structured narrative review of the existing literature addressing the major barriers and enablers for health systems implementation reform. This review assesses the extent to which people issues and people-centred practices are considered in policy implementation research of GeneXpert. The aim of this section of the dissertation is to identify and map-out literature considering the human experiences and relationships of frontline health workers and how these may intersect with hardware, contextual and social systemic factors, that may potentially mediate the implementation of GeneXpert TB diagnostic policy. Part C: This section presents the background, methodology, findings and interpretations from the research, as a journal-ready manuscript. This paper seeks to contribute to the policy implementation literature in the field of HPSR from the perspective of centering nurses' lived experience – especially nurses who are overburdened and undervalued – as imperative in the field of inquiry. The main findings reflect that nurses are burdened by the pressure to meet policy targets, the encumbrance to enforce administrative and bureaucratic procedure, and the minimal platforms or pathways to input on challenges and innovations back to higher level management and decision makers. Within the context of top-down, target-driven and highly structured and standardized operational processes for diagnosing TB, nurses navigate multiple overlapping and contradictory modes of being in their interactions with patients as a response to these pressures. This paper seeks to offer voice to nurses’ experiences of implementing TB diagnostic policy in PHC settings in SA considering its relationship with broader systemic and contextual influences. It also raises particular issues about tensions between efforts to achieve efficiency and effectiveness through enforcing the system, and facilitating people-centered and responsive practices in implementation.